Mesenchymal stem cell-derived extracellular vesicles ameliorate renal interstitial fibrosis via the miR-13474/ADAM17 axis - Linru Shi; Yuyan Hu; Houcheng Zeng; Hui Shi; Wenrong Xu; Yaoxiang Sun; Hong Chu; Cheng Ji; Hui Qian (Scientific Reports, 2024)
Abstract Renal interstitial fibrosis (RIF) is a prevalent consequence of chronic renal diseases, characterized by excessive extracellular matrix (ECM) deposition. A Disintegrin and Metalloprotease 17 (ADAM17), a transmembrane metalloproteinase, plays a central role in driving renal fibrosis progression by activating Notch 1 protein and the downstream TGF-β signaling pathway. Our study investigated potential therapeutic interventions for renal fibrosis, focusing on human umbilical cord mesenchymal stem cell-derived extracellular vesicles (hucMSC-EVs). We found that hucMSC-EVs inhibit ADAM17, thereby impeding renal fibrosis progression. Analysis of hucMSC-EVs miRNA profiles revealed significant enrichment of miR-13474, which effectively targeted and inhibited ADAM17 mRNA expression, subsequently suppressing Notch1 activation, TGF-β signaling, and collagen deposition. Overexpression of miR-13474 enhanced hucMSC-EVs' inhibitory effect on renal fibrosis, while its downregulation abolished this protective effect. Our findings highlight the efficacy of hucMSC-EVs overexpressing miR-13474 in mitigating renal fibrosis via ADAM17 targeting. These insights offer potential therapeutic strategies for managing renal fibrosis.